Gender and Agriculture in the Information Society - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The 5th CTA Observatory Meeting was a major step forward in creating a dialogue among ACP countries and with other regions of the world on the role of ICTs in helping rural women overcome the obstacles that they experience daily in their lives...